Probabilistic transmission system planning - Li, Wenyuan (Hoboken, N.J. : John Wiley & Sons/IEEE Press, 2011)
'The book is composed of 12 chapters and three appendices, and can be divided into four parts. The first part includes Chapters 2 to 7, which discuss the concepts, models, methods and data in probabilistic transmission planning. The second part, Chapters 8 to 11, addresses four essential issues in probabilistic transmission planning applications using actual utility systems as examples. Chapter 12, as the third part, focuses on a special issue, i.e. how to deal with uncertainty of data in probabilistic transmission planning. The fourth part consists of three appendices, which provide the basic knowledge in mathematics for probabilistic planning. Please refer to the attached table of contents which is given in a very detailed manner'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electric power transmission -- Planning -- Statistical methods; Probabilities